Heterogeneity assessment of vaccine‐induced effects using point‐of‐care surrogate neutralization test for severe acute respiratory syndrome coronavirus 2. Issue 7 (9th June 2022) - Watanabe, Yoshiyuki; Matsuba, Ikuro; Watanabe, Karin; Kunishima, Tomoyuki; Takechi, Yukako; Takuma, Tetsuo; Araki, Yasushi; Hirotsu, Nobuo; Sakai, Hiroyuki; Oikawa, Ritsuko; Danno, Hiroki; Fukuda, Masakazu; et al.
Abstract: Introduction: Coronavirus disease (COVID‐19) caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) has become a global pandemic even after vaccination. We aimed to identify immunological heterogeneity over time in vaccinated healthcare workers using neutralization antibodies and neutralizing activity tests. Methods: Serum samples were collected from 214 healthcare workers before vaccination (pre) and on days 22, 90, and 180 after receiving the first dose of BNT162b2 vaccine (day 0). Neutralization antibody (NAb, SARS‐CoV‐2 S‐RBD IgM/IgG) titers and two kinds of surrogate virus neutralization tests (sVNTs) were analyzed (UMIN000043851). Results: The NAb (SARS‐CoV‐2 S‐RBD IgG) titer peaked on day 90 after vaccination (30, 808.0 μg/ml ± 35, 211; p  < 0.0001) and declined on day 180 (11, 678.0 μg/ml ± 33, 770.0; p  < 0.0001). The neutralizing activity also peaked on day 90 and declined with larger individual differences than those of IgG titer on day 180 (88.9% ± 15.0%, 64.8% ± 23.7%, p  < 0.0001). We also found that the results of POCT‐sVNT (immunochromatography) were highly correlated with those of conventional sVNT (ELISA). Conclusions: Neutralizing activity is the gold standard for vaccine efficacy evaluation. Our results using conventional sVNT showed large individual differences in neutralizing activity reduction on day 180 (64.8% ± 23.7%), suggesting an association with the difference in vaccine efficacy. POCT‐sVNT is rapid and user‐friendly; it might be used for triage in homes, isolation facilities, and event venues without restrictions on the medical testing environment. Abstract : Four points of NAbs antibody assay and sVNT. A: NAbs（SARS‐CoV‐2 S‐RBD IgG / IgM）measurement before and after vaccine on Day 22, Day 90, Day 180. The data presented represent the log of the neutralization titer for NAbs. The P values presented in A was calculated using unpaired two‐tailed Students t‐tests. B: sVNT measurement before and on Day 22, Day 90, Day 180 after the first vaccination. The dotted lines represent the cutoff at 30% inhibition. The P values presented in A was calculated from unpaired two‐tailed Students t‐tests.